Optimalisasi Keterampilan Mahasiswa Melalui Hands-On Keperawatan Kritis - Baidhowy, Arief Shofyan; Sarinti, Sarinti; Lazuardi, Nugroho; Keysha, Nayandra; Suharto, Suharto; Haryanti, Richta Puspita (Jurnal LINK, 2025)
Student competence in critical care is of particular concern. Various studies highlight barriers and deficiencies in knowledge and skills. These gaps can adversely affect students' readiness to provide quality care to critically ill patients. This community service aims to improve knowledge in dealing with critical nursing conditions. The method used was hands on / training with a blended learning approach demonstrating 4 skills to 202 participants consisting of students of Poltekkes Kemenkes Semarang. The skills provided were Ventilator, ECG interpretation, Set Titration and Acid-Base analysis. Data analysis test using the Paired t-test. The results of this community service found that knowledge increased from an average of 68 to 92. The results of the Paired t-test show that there is a significant difference between the pretest and posttest scores, with a p-value of 0.001. This critical nursing training is effective in improving student readiness through increased knowledge, skills and basic competencies for students.